Analisis Penggunaan Kahoot dalam Meningkatkan Partisipasi Siswa pada Pembelajaran Bahasa Arab di MTs Al Washliyah 01 Medan - Yasyfin Halim Ali (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the effectiveness of the use of interactive learning media Kahoot in increasing student participation in Arabic language learning in class VIII MTs Al Washliyah 01 Medan. The background of this study is based on the low involvement of students in Arabic language learning which tends to be passive and monotonous. The research method used is quantitative descriptive with data collection techniques in the form of questionnaires using a Likert scale and class observation. The research subjects were 35 students, and the data were analyzed using descriptive statistics in the form of percentages and averages. The results showed that the use of Kahoot had a positive impact on five indicators of student participation, namely learning pleasure, active asking and answering, understanding the material, enthusiasm for learning, and perceptions of a pleasant learning atmosphere. All indicators recorded a high average score between 4.00 and 4.23. As many as 85.71% of students stated that they felt more active and motivated when using Kahoot. In addition, the learning atmosphere became more lively and competitive in a healthy way, although there were still technical obstacles such as limited devices and internet connections. The conclusion of this study is that Kahoot is effective in increasing student participation and can be used as an innovative alternative in learning Arabic that is more interactive, fun, and in accordance with developments in educational technology.